Intraoperative sonography during lumbar laminectomy: work in progress. - Gooding, G A; Boggan, J E; Weinstein, P R (American Journal of Neuroradiology, 1984)
The feasibility of intraoperative sonography during lumbar laminectomy was demonstrated in six cases. The most obvious advantage was the ability to image the spinal canal anterior to the spinal cord or cauda equina, which cannot be seen directly from the posterior operative approach. A water bath of warm saline serves as an ideal acoustic window. This technique has the potential to be a significant contribution to intraoperative exploration and localization.